2020
DOI: 10.3892/ijmm.2020.4721
|View full text |Cite
|
Sign up to set email alerts
|

Expression level of NEAT1 differentiates benign and malignant thyroid nodules by regulating NEAT1/miR‑9/PTEN and NEAT1/miR‑124/PDCD6 signalling

Abstract: The incidence of thyroid nodules has been increasing worldwide; however, there are currently no feasible and robust methods to differentiate malignant thyroid nodules from benign thyroid nodules. The present study aimed to establish a practical method to determine the malignancy of thyroid nodules. Reverse transcription-quantitative PcR and western blot analyses were performed to compare the levels of long non-coding RNA nuclear enriched abundant transcript 1 (NEAT1), microRNA (miR)-9, miR-124, PTEN and progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…In patients with colorectal cancer, NEAT1 showed a significant predictive role in differentiating between patients and normal controls (AUC = 0.9471; P < 0.01) ( Peng et al, 2017 ). A comparable finding was also observed in COPD cases (AUC = 0.869, 95% CI: 0.817–0.921) ( Ming et al, 2019 ), myocardial infarction (AUC = 0.822; P < 0.01) ( Chen et al, 2020 ), and malignant thyroid nodules (AUC = 0.9304, P < 0.01) ( Zhao et al, 2020 ). With respect to MALAT1, many studies have indicated its role in the diagnosis of various diseases, like non-traumatic osteonecrosis of the femoral head (AUC = 0.681, P = 0.009) ( Jin et al, 2020 ), diabetic retinopathy (AUC = 0.741, P < 0.001) ( Shaker et al, 2019a , Shaker et al, 2019b ), and diabetic nephropathy (AUC = 0.914, P < 0.01) ( Zhou et al, 2020 ).…”
Section: Discussionsupporting
confidence: 66%
“…In patients with colorectal cancer, NEAT1 showed a significant predictive role in differentiating between patients and normal controls (AUC = 0.9471; P < 0.01) ( Peng et al, 2017 ). A comparable finding was also observed in COPD cases (AUC = 0.869, 95% CI: 0.817–0.921) ( Ming et al, 2019 ), myocardial infarction (AUC = 0.822; P < 0.01) ( Chen et al, 2020 ), and malignant thyroid nodules (AUC = 0.9304, P < 0.01) ( Zhao et al, 2020 ). With respect to MALAT1, many studies have indicated its role in the diagnosis of various diseases, like non-traumatic osteonecrosis of the femoral head (AUC = 0.681, P = 0.009) ( Jin et al, 2020 ), diabetic retinopathy (AUC = 0.741, P < 0.001) ( Shaker et al, 2019a , Shaker et al, 2019b ), and diabetic nephropathy (AUC = 0.914, P < 0.01) ( Zhou et al, 2020 ).…”
Section: Discussionsupporting
confidence: 66%
“…Another highly represented in tumors and actively studied lncRNA NEAT1 (nuclear-enriched abundant transcript 1) was regulated in four types of cancer: breast cancer, hepatocellular carcinoma, nasopharyngeal carcinoma, and malignant thyroid nodules [ 81 , 82 , 83 , 84 ]. All these studies were conducted both on cell lines and on clinical samples from patients; xenografts of mice were used in two studies [ 81 , 82 ].…”
Section: Long Non-coding Rnas In Dysregulation Of Mir-124 Target Gene...mentioning
confidence: 99%
“…All these studies were conducted both on cell lines and on clinical samples from patients; xenografts of mice were used in two studies [ 81 , 82 ]. Four interactomes were identified: NEAT1/miR-124-3p/ATGL (adipose triglyceride lipase), NEAT1/miR-124-3p/p65 (NF-κB), NEAT1/miR-124/PDCD6 (programmed cell death 6), NEAT1/miR-124-3p/STAT3 (signal transducer and activator of transcription 3) [ 81 , 82 , 83 , 84 ], which is also shown in Figure 2 b. These interactomes increased cell proliferation, migration, invasion, EMT and inhibit apoptosis in vitro and initiate tumor growth in immune-deficient mice in vivo.…”
Section: Long Non-coding Rnas In Dysregulation Of Mir-124 Target Gene...mentioning
confidence: 99%
“…In addition, PI3K/AKT/mTOR, as a classic signaling pathway in tumors, is often caused by abnormal PTEN gene function, resulting in inhibition of cell apoptosis, acceleration of cell cycle, promotion of angiogenesis and tumor invasion and metastasis [ 25 27 ]. The studies found that Neat1 can inhibit the expression level of PTEN in laryngeal cancer [ 28 ] and thyroid carcinoma [ 29 ] to promote malignant biological behavior of tumors. Previous research by our group also found that RBM10 can regulate RAP1/AKT/CREB to play a tumor suppressor role [ 30 ].…”
Section: Introductionmentioning
confidence: 99%